Balancing evolving logics: Business model change in the Leibniz research museums. (23rd November 2018) - Decker-Lange, Carolin; Singer, Marie-Noëlle; Schrader, Florian
Abstract: This study shows how stakeholders' evolving logics drive business model change over time. Using secondary data from the Leibniz research museums in Germany in a longitudinal content analysis, we relate logics as drivers of business model change in a context that is shaped by the interests of multiple stakeholder groups. Our findings illustrate how stakeholders' varying emphases on economic, cultural, and political logics affect the content, structure and governance of the activities constituting the business models of the research museums. They lead to an increasing need for the demonstration of value creation and the identification of new sources of revenue. The strength of the impact of these logics depends on the individual abilities of the research museums to bargain for their business models. Overall, our study sheds light on the drivers of business model change in public organizations and the accompanying macro-level factors in the German science system.